2023
DOI: 10.3390/antibiotics12030585
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Anthranilamide Peptidomimetic Design to Selectively Target Planktonic Bacteria and Biofilm

Abstract: There is a pressing need to develop new antimicrobials to help combat the increase in antibiotic resistance that is occurring worldwide. In the current research, short amphiphilic antibacterial and antibiofilm agents were produced by tuning the hydrophobic and cationic groups of anthranilamide peptidomimetics. The attachment of a lysine cationic group at the tail position increased activity against E. coli by >16-fold (from >125 μM to 15.6 μM) and greatly reduced cytotoxicity against mammalian cells (fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Overall, the structure–activity relationship analysis for these peptidomimetics suggested that the optimal combination for antibacterial activity against Gram‐positive S. aureus was heptyl alkyl chain and a lysine group or a guanidine group as demonstrated in the last three series of analogues. Therefore, compounds 6 c , 9 a , 12 a , 12 c , 13 a which embodied these characteristics were found to be the most potent compounds (MIC=8 μM) against S. aureus in this study, and are much more potent than the known membrane active antibiotic Colistin which possesses an MIC of 125 μM against S. aureus [41] . Interestingly, introducing a linker of a suitable length between guanidine and piperazine favored antibacterial activity against Gram‐negative E. coli .…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Overall, the structure–activity relationship analysis for these peptidomimetics suggested that the optimal combination for antibacterial activity against Gram‐positive S. aureus was heptyl alkyl chain and a lysine group or a guanidine group as demonstrated in the last three series of analogues. Therefore, compounds 6 c , 9 a , 12 a , 12 c , 13 a which embodied these characteristics were found to be the most potent compounds (MIC=8 μM) against S. aureus in this study, and are much more potent than the known membrane active antibiotic Colistin which possesses an MIC of 125 μM against S. aureus [41] . Interestingly, introducing a linker of a suitable length between guanidine and piperazine favored antibacterial activity against Gram‐negative E. coli .…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, compounds 6 c, 9 a, 12 a, 12 c, 13 a which embodied these characteristics were found to be the most potent compounds (MIC = 8 μM) against S. aureus in this study, and are much more potent than the known membrane active antibiotic Colistin which possesses an MIC of 125 μM against S. aureus. [41] Interestingly, introducing a linker of a suitable length between guanidine and piperazine favored antibacterial activity against Gram-negative E. coli. Finally, comparing the guanidines to their corresponding guanidine hydrochloride salts, the guanidine hydrochloride salts possessed similar or less potency than the corresponding guanidines.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Additionally, compound 1A underwent transformation via reaction with various acid chlorides, subsequent deprotection, and treatment with Nα,Nε-Di-Boc-L-lysine hydroxysuccinimide ester, thereby affording the formation of a series of amine compounds 15 – 17 upon BOC group deprotection. The detailed procedure of the intermediate and the final compounds are presented in references [ 40 , 53 ]. The Supplementary Information contains the data for all the final compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Anthranilamide possesses a special chemical configuration characterized by amide functional groups which makes it a useful building block for the synthesis of organic compounds [ 40 ]. Prior investigations have documented that derivatives derived from anthranilamides have inhibitory effects against bacteria [ 40 ], can disrupt bacterial biofilms [ 40 ], and also have antiviral properties against alphaviruses [ 41 ]. The objective of this study was to investigate the antiviral effectiveness of anthranilamide-based peptide mimetics against two distinct viral pathogens, MHV-1 and HSV-1.…”
Section: Introductionmentioning
confidence: 99%